High Number of Activated CD8+ T Cells Targeting HIV Antigens Are Present in Cerebrospinal Fluid in Acute HIV Infection. (1st May 2017) - Kessing, Cari F.; Spudich, Serena; Valcour, Victor; Cartwright, Pearline; Chalermchai, Thep; Fletcher, James L. K.; Takata, Hiroshi; Nichols, Carmen; Josey, Benjamin J.; Slike, Bonnie; Krebs, Shelly J.; Sailsuta, Napapon; et al.
Abstract : Background: Central nervous system (CNS) infiltration by CD8 + T cells is associated with neuroinflammation in many neurodegenerative diseases, including HIV-associated dementia. However, the role of CD8 + T cells in the CNS during acute HIV infection (AHI) is unknown. Methods: We analyzed the phenotype, gene expression, T cell receptor (TCR) repertoire, and HIV specificity of CD8 + T cells in cerebrospinal fluid (CSF) of a unique cohort captured during the earliest stages of AHI (n = 26), chronic (n = 23), and uninfected (n = 8). Results: CSF CD8 + T cells were elevated in AHI compared with uninfected controls. The frequency of activated CSF CD8 + T cells positively correlated to CSF HIV RNA and to markers of CNS inflammation. In contrast, activated CSF CD8 + T cells during chronic HIV infection were associated with markers of neurological injury and microglial activation. CSF CD8 + T cells in AHI exhibited increased functional gene expression profiles associated with CD8 + T cells effector function, proliferation, and TCR signaling, a unique restricted TCR Vbeta repertoire and contained HIV-specific CD8 + T cells directed to unique HIV epitopes compared with the periphery. Conclusions: These results suggest that CSF CD8 + T cells in AHI expanding in the CNS are functional and directed against HIV antigens. These cells could thus play a beneficial role protective of injury seen in chronic HIV infection if combination antiretroviral therapy is initiated early. Abstract : Supplemental Digital Content is Available in the Text.